Antibacterial Peptide Protocols - Shafer, William.; Shafer, William. (Methods in Molecular Biology,, 1997)
In Antibacterial Peptide Protocols, leading authorities review for the first time in one volume all the major biochemical, molecular, bacteriological, and physical techniques available to assess antimicrobial peptides. These state-of-the-art methods ensure easily reproducible results in such important procedures as the isolation and characterization of antimicrobial peptides, the molecular characterization of genes encoding antimicrobial peptides, and the use of expression systems to isolate peptides. Bioassays and microbial genetic techniques are also included, as are antibacterial assays as the final readout system. These methods detailed in Antibacterial Peptide Protocols will play an important role in the treatment of infectious diseases, particularly with the increasing problem of multidrug-resistant microbes and the relative dearth of new antibiotics being provided by pharmaceutical companies.